The evolution of coorporation in infinitely repeated games: Experimental evidence - Pedro Dal Bó; Guillaume R. Fréchette (Brown University, Department of Economics, 2007)
A usual criticism of the theory of infinitely repeated games is that it does not provide sharp predictions since there may be a multiplicity of equilibria. To address this issue we present experimental evidence on the evolution of cooperation in infinitely repeated prisoners' dilemma games as subjects gain experience. We find that cooperation decreases with experience when it cannot be supported as an equilibrium outcome. More interestingly, the converse is not necessarily true: cooperation does not always increase with experience when it can be supported as an equilibrium outcome. Nor is a more stringent condition, risk dominance, sufficient for cooperation to arise. However, subjects do learn to cooperate when the payoff to cooperation and the importance of the future is high enough. These results have important implications for the theory of infinitely repeated games. While we show that cooperation may prevail in infinitely repeated games, the conditions under which this occurs are more stringent than the sub-game perfect conditions usually considered.
Keywords: 330; Wiederholte Spiele; Kooperatives Spiel; Spieltheorie